Relevance of Traditional Indian Medical Concepts in Psychosomatic Medicine - Sood, Mamta; Singh, Saurabh K; Chadda, Rakesh K (Annals of the National Academy of Medical Sciences (India), 2017)
Traditional medicine comprises of health related knowledge, skill and practices indigenous to different cultures. India has a rich heritage of traditional system of medicine that emphasizes the close link between mind and body like the psychosomatic medicine. The government of India has set up a department of AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha and Homoeopathy). The importance of life style, dietary and environmental factors in the development of various psychosomatic disorders has been emphasized in all the Indian traditional systems of medicine. Although studies have shown acceptability and beneficial role of traditional medicinal practices, efforts should be made to tease out and conduct research on the practices, which can help physicians in improving well-being of the patients. More rigorous research is required in the direction to generate evidence base for these practices so that their full potential can be realized.
Keywords: Traditional Indian systems of medicine; AYUSH; Ayurveda; ayurvedic medicine; psychosomatic disorders